Low-Dose Sublingual Ketamine Does Not Modulate Experimentally Induced Mechanical Hyperalgesia in Healthy Subjects - Slater, Helen; Graven-Neilsen, T.; Wright, Anthony; Schug, S. (Wiley-Blackwell Publishing, Inc, 2012)
Objective: Musculoskeletal pain has been associated with N-methyl-d-aspartate (NMDA) receptor-mediated mechanisms. This randomized controlled trial (RCT) investigated the effect of the NMDA receptor antagonist ketamine (25 mg sublingually) on modulating experimental muscle pain. Design: Two groups (N = 11/group) of age- and sex-matched healthy subjects performed eccentric exercise using the nondominant arm wrist extensors (time 0) to induce muscle soreness 24 hours later (time 1). Intervention: Immediately prior to exercise, subjects were administered either a 25 mg ketamine lozenge or a placebo. At time 1, experimental muscle pain was augmented by injection of hypertonic saline into the extensor carpi radialis brevis (ECRB) muscle of the exercised arm. Outcome Measures: Pressure pain thresholds (PPTs), muscle soreness, muscle pain intensity (electronic visual analog scale [VAS]), and maximal wrist extension force were assessed at time 0 (pre- and postexercise) and at time 1 (pre-, during, and post saline-induced pain). Results: Regardless of group, PPT was reduced at ECRB (P < 0.021) and at the common extensor origin (P < 0.034) at time 1 preinjection compared with time 0 pre-exercise. At time 1, elevated levels of muscle soreness and force attenuation were similar between groups compared with time 0 pre-exercise (P < 0.0001), and similar hypertonic saline-induced pain areas and pain intensity profiles were evident. Conclusion: In comparison with placebo, a single low-dose sublingual pharmacological intervention targeting the processes of sensitization via antagonism of NMDA receptors did not modulate the effects of acute experimentally induced mechanical hyperalgesia, suggesting a higher dose or repeat doses may be required.